Dynamic Stabilization with Active Locking Plates Delivers Faster, Stronger, and More Symmetric Fracture-Healing. (16th March 2016) - Bottlang, Michael; Tsai, Stanley; Bliven, Emily K.; von Rechenberg, Brigitte; Klein, Karina; Augat, Peter; Henschel, Julia; Fitzpatrick, Daniel C.; Madey, Steven M.
Abstract : Background: Axial dynamization of fractures can promote healing, and overly stiff fixation can suppress healing. A novel technology, termed active plating, provides controlled axial dynamization by the elastic suspension of locking holes within the plate. This prospective, controlled animal study evaluated the effect of active plates on fracture-healing in an established ovine osteotomy model. We hypothesized that symmetric axial dynamization with active plates stimulates circumferential callus and delivers faster and stronger healing relative to standard locking plates. Methods: Twelve sheep were randomly assigned to receive a standard locking plate or an active locking plate for stabilization of a 3-mm tibial osteotomy gap. The only difference between plates was that locking holes of active plates were elastically suspended, allowing up to 1.5 mm of axial motion at the fracture. Fracture-healing was analyzed weekly on radiographs. After sacrifice at nine weeks postoperatively, callus volume and distribution were assessed by computed tomography. Finally, to determine their strength, healed tibiae and contralateral tibiae were tested in torsion until failure. Results: At each follow-up, the active locking plate group had more callus (p < 0.001) than the standard locking plate group. At postoperative week 6, all active locking plate group specimens had bridging callus at the three visible cortices. In standard locking plate group specimens, only 50% of these cortices had bridged. Computed tomography demonstrated that all active locking plate group specimens and one of the six standard locking plate group specimens had developed circumferential callus. Torsion tests after plate removal demonstrated that active locking plate group specimens recovered 81% of their native strength and were 399% stronger than standard locking plate group specimens (p < 0.001), which had recovered only 17% of their native strength. All active locking plate group specimens failed by spiral fracture outside the callus zone, but standard locking plate group specimens fractured through the osteotomy gap. Conclusions: Symmetric axial dynamization with active locking plates stimulates circumferential callus and yields faster and stronger healing than standard locking plates. Clinical Relevance: The stimulatory effect of controlled motion on fracture-healing by active locking plates has the potential to reduce healing complications and to shorten the time to return to function.